STUDENTS’ PERCEPTION OF USING THE SONGS TO IMPROVE PRONUNCIATION - Situmeang, Lisda Via Grace; Panjaitan, Nelson Balisar (STKIP PGRI Situbondo, 2024)
Pronunciation is an essential aspect of language learning, and it can be a challenging skill for many students to master. However, research has shown that using songs in language learning can be an effective way to improve pronunciation skills (Chen & Liang, 2018; Godwin-Jones, 2019; Lee, 2021; Zahra & Hadi, 2020). One reason why songs may be effective for improving pronunciation is that they provide learners with a model for correct pronunciation. When students listen to and sing along with songs, they are exposed to the correct pronunciation of words and phrases, which can help them to develop a more accurate pronunciation themselves. This research uses qualitative methods, especially interview analysis. One of the most crucial sources in qualitative research to gain an in-depth understanding of how people experience, feel, and interpret the social world is the interview (Dong, 2012). According to Oakley, a qualitative interview is a form of framework where practices and standards can be reached, pushed, and reinforced in addition to being documented (Nasreen, 2019). This research aims to determine students’ perceptions regarding the use of songs as a tool to improve English pronunciation easily. This research was guided by three main research questions: 1. What are the students' perceptions of using English songs to improve their pronunciation? 2. Can English songs help EFL students get better at pronouncing words? 3. How could using music help students pronounce words more fluently? Each song aimed to explore a specific aspect of songs for pronunciation. This study aims to gain insight into the various ways students use songs to learn language, such as saying words and hearing the rhythm and lyrics to facilitate vocabulary learning. Learning can be made more engaging and entertaining by using songs. While learning the target language, pupils feel at ease in a calm environment and pick up the language (as seen by their better pronunciation). They become more open to learning due to lowering their affective filter. Songs also aid students in better comprehending and pronouncing key phonological elements.